2016
DOI: 10.1371/journal.pone.0159473
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screen in Drosophila Larvae Links ird1 Function to Toll Signaling in the Fat Body and Hemocyte Motility

Abstract: To understand how Toll signaling controls the activation of a cellular immune response in Drosophila blood cells (hemocytes), we carried out a genetic modifier screen, looking for deletions that suppress or enhance the mobilization of sessile hemocytes by the gain-of-function mutation Toll10b (Tl10b). Here we describe the results from chromosome arm 3R, where five regions strongly suppressed this phenotype. We identified the specific genes immune response deficient 1 (ird1), headcase (hdc) and possibly Rab23 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…It was also observed that lamellocytes downregulate hdc expression when leaving the lymph gland [28]. These findings suggest that Hdc may exert a repressive role during hematopoiesis, which is also corroborated by the observation that hdc alleles suppress the disruption of the sessile compartment induced by Toll 10b [62].…”
Section: Discussionmentioning
confidence: 78%
“…It was also observed that lamellocytes downregulate hdc expression when leaving the lymph gland [28]. These findings suggest that Hdc may exert a repressive role during hematopoiesis, which is also corroborated by the observation that hdc alleles suppress the disruption of the sessile compartment induced by Toll 10b [62].…”
Section: Discussionmentioning
confidence: 78%
“…Overexpression of Toll 10B or loss of Jumeau (Jumu), a member of the forkhead transcription factor family, throughout the lymph gland, induces lamellocyte differentiation as well as nuclear translocation of Dif (Dorsal-related immunity factor), indicating a cell autonomous role of Toll activation in lamellocyte differentiation in the lymph gland (Hao and Jin 2017). Loss of ird1 ( immune response-deficient 1 ) enhances lamellocyte formation in Toll 10B mutants and in fact induces lamellocyte formation on its own (Schmid et al 2016). Toll also plays a role in the cellular response to wasp parasitization (Louradour et al 2017).…”
Section: Drosophila Blood Cell Typesmentioning
confidence: 99%
“…During this process, the circulating hemocyte population also increases as the sessile pool is released into the hemolymph (Honti et al 2009). Constitutive activation of Toll signaling in Toll 10B mutants also disrupts the sessile hemocyte pools, a phenotype that is suppressed in an ird1 mutant (Schmid et al 2016).…”
Section: Sites Of Hematopoietic Developmentmentioning
confidence: 99%
“…Another pathway overrepresented in our RNA-seq differential expression data from Svp i fat bodies was the immune response pathway. The Drosophila fat body plays a key role in the expression of antimicrobial peptides and in hemocyte biogenesis during immune activation (Schmid et al 2014(Schmid et al , 2016Vanha-Aho et al 2015;Yang and Hultmark 2016). We found that loss of Svp led to increased expression of immune genes and improved immune function using the septic injury infection model.…”
Section: Discussionmentioning
confidence: 57%